Quadriceps tendon rupture associated with anabolic steroids and growth hormone: a case report - Özakın, Engin; Çalışır, Cüneyt; Karakılıç, Muhammed Evvah; Acar, Nurdan (The European Research Journal, 2018)
Androgenic and human growth hormone derivatives have to potential to increase athletic performance despite increased risk of serious adverse effects. The risk of tendon rupture is very high in the anabolic androgenic steroid users. A 51-year-old male admitted to the emergency department with left knee pain following sport training. He had a history combination of androgenic hormones and insuline growth factor -1 use. Magnetic resonance imaging showed swelling, heterogeneity and partial discontinuity of the quadriceps tendon. Use of performance enhancing drugs has become a serious public health problem. Due to increase of abuse today it is possible to encounter more side effects in the future and has to be considered as a growing public health problem.